الاستثمار في عملة البتكوين - Rachmat Murdani Mursal (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
ABSTRACT Rachmat Murdani Mursal: "Investment in cryptocurrencies, Bitcoin as a model (a jurisprudential-analytical study)" Dealing with encrypted digital currencies is one of the contemporary issues in financial transactions, and one of the most important forms of dealing with these currencies is investing in Bitcoin. Many people invest their money in this field without knowing the risks that will affect them, as well as knowing the provisions related to it. This research aims to know the Shariah ruling on investing in the Bitcoin currency, its method, and its implications. In writing this research, the researcher took a descriptive and analytical approach, and the researcher found that investing in the bitcoin currency is not without notes and legal prohibitions, including: that investing in this currency did not meet the legal controls for investment, where there is deception, ignorance, risk, and harm, It was not compatible with the purposes of investment, such as: the purpose of saving and developing money, and the purpose of economic and social development. Investment in this currency has had very dangerous effects, such as monetary instability, tax evasion, and a decline in productive investments. The researcher recommends government agencies to address this currency (Bitcoin) and its sisters, and to establish a legal regulation that shows its issuance, the field of dealing with it, and its trading mechanisms. The researcher also recommends the Central Bank to work on issuing an official encrypted currency that is fully compatible with the purposes and controls of Islamic law. Keywords: investment, cryptocurrency, bitcoin